EFEKTIVITAS AIR SEDUHAN TEH HITAM (Camellia sinensis) DALAM MENURUNKAN AKUMULASI PLAK - Idham Halid; Asio Asio; Karin Tika Fitria (Poltekkes Kemenkes Jambi, 2021)
Background: Black tea (Camellia sinensis) is believed to have considerable benefits and efficacy for life and health. This study aims to determine the effectiveness of gargling steeped black tea leaves in reducing plaque index. Methods: This research is a quasi-experimental study with a pretest and posttest design. A total of 10 respondents participated in this study. Every night the respondents were asked to brush their teeth without toothpaste and followed by gargling with Aquadest, brewing black tea and Chlorhexidine for 5 days each, and measuring the plaque index at pre and post treatment. Statistical analysis t-test was used to test the mean difference between before and after treatment and ANOVA to compare differences in plaque index changes between the three groups. Results: Significant differences in plaque index values ​​before and after treatment were found in the group that rinsed with tea (p = 0.019) and in the group that rinsed with chlorhexidine (p = 0.005). However, there was no significant difference between gargling with black tea and gargling with Chlorhexidine (p = 0.222). There was a significant difference (p=0.010) in plaque index changes between the three groups. Conclusion: Gargling with black tea has been shown to be effective in reducing plaque formation